Cover Image. Issue 29 (23rd September 2020) - Saito, Kohei; Watabe, Yuya; Miyazaki, Takaaki; Takayanagi, Toshiyuki; Hasegawa, Jun‐ya
Abstract : The cover image is based on the Original Article Spin‐inversion mechanisms in O2 binding to a model heme compound: A perspective from nonadiabatic wave packet calculations by Yuya Watabe et al., https://doi.org/10.1002/jcc.26409